1982
DOI: 10.1111/j.1365-2389.1982.tb01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barley plants on the decomposition of 14C‐labelled soil organic matter

Abstract: The effect of barley plants on the rate of decomposition of soil organic matter over a 6-week period was studied using soil that had been previously labelled by incubation with IF-labelled ryegrass for 1 year. The plants reduced the loss of ' 4 2 0 , from soil by 70 per cent over 42 days. About half of the reduction was accounted for by the uptake of labelled C by the plant roots, very little '42 label being associated with the shoot.Chemical fractionation of the root showed that the IF was chemically incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 25 publications
2
39
1
1
Order By: Relevance
“…Conversely, the retention of green manure-derived N in organic form was 25% higher in cropped than in uncropped treatments. These observations parallel those of studies examining C dynamics in the rhizosphere which reported suppression of the decomposition of ~4C-labelled organic substrate by the presence of a crop (Martin, 1987;Reid and Goss, 1982;Sparling et al, 1982). Our results differ, however, from those of Haider et al (1987) who observed higher mineralization of organic N in planted than in unplanted soils.…”
Section: Discussioncontrasting
confidence: 46%
“…Conversely, the retention of green manure-derived N in organic form was 25% higher in cropped than in uncropped treatments. These observations parallel those of studies examining C dynamics in the rhizosphere which reported suppression of the decomposition of ~4C-labelled organic substrate by the presence of a crop (Martin, 1987;Reid and Goss, 1982;Sparling et al, 1982). Our results differ, however, from those of Haider et al (1987) who observed higher mineralization of organic N in planted than in unplanted soils.…”
Section: Discussioncontrasting
confidence: 46%
“…It could reduce the supply of nutrients to plants by two methods: first, increasing C availability causes net immobilization, reducing the concentration of plant-available N, and second, it could also reduce the rate N flow into the NH 4 pool, reducing the NH 4 supply . Root exudation could also reduce SOM decomposition in the rhizosphere, as has been observed in several studies Goss, 1982, 1983;Sparling et al, 1982).…”
Section: Discussionmentioning
confidence: 76%
“…Decomposition of labeled plant material was markedly lowered in the presence of cultivated plant cover or in natural grasslands when compared to bare soil controls (Shields and Paul, 1973;Jenkinson, 1977). When 14C-labeled plant material was decomposed in soil planted with maize, ryegrass, wheat or barley, 14CO2 release from the soil was reduced compared to bare soil controls during experiments under controlled conditions (Reid and Goss, 1982;1983;Sparling et al, 1982). It was generally suggested that this negative effect of living roots on soil organic matter decomposition was probably due to the competition between the living roots and the rhizosphere microflora for substrates and due to the changed physical and chemical conditions by roots.…”
Section: Resultsmentioning
confidence: 88%